Mutation Profile via Next-Generation Sequencing in Patients with Colorectal Adenocarcinoma and Its Clinicopathological Correlation - Osman, Sibel; Kahraman Çetin, Nesibe; Erdoğdu, İbrahim Halil and Meteoğlu, İbrahim (Turkish Journal of Gastroenterology, 2023)
Background/Aims: Recent studies that reveal the molecular profiles of colorectal carcinomas have demonstrated tumor heterogeneity. Characterization of colorectal carcinoma-specific genomic alterations is essential for developing more successful and targeted treat- ment protocols. Moreover, it is vital in elucidating the pathogenesis and mechanisms of resistance against treatment and predicting prognosis. Materials and Methods: The study included 73 cases diagnosed with colorectal carcinomas and subjected to molecular analysis by the next-generation sequencing. The association between the clinicopathologic parameters and pathogenic mutations detected in 32 genes was evaluated. Results: Pathogenic mutations were determined in a total of 24 genes. The Cell Division Cycle 27 (CDC27), Kirsten rat sarcoma viral proto-oncogene (KRAS), serine/threonine protein kinase B-raf (BRAF), phosphatase and tensin homolog, breast cancer 2 (BRCA2), and phosphotidylinositol-4,5-biphosphate 3-kinase (PIK3CA) mutations were determined at higher rates, with the adenomatous polypo- sis coli mutation determined at a lower rate than in the literature. There were significant positive correlations between CDC27 and phosphatase and tensin homolog (PTEN), PTEN and BRCA2, and PTEN and adenomatous polyposis coli (APC) concomitant muta- tions, whereas negative correlations were present between BRAF and KRAS. Statistically significant relationships were present between KRAS exon 2 and mucinous morphology, PIK3CA and absence of perineural invasion, BRAF and tumor differentiation/localization, MutS homolog 3 (MSH3) and tumor diameter, and BRCA2 and absence of lymph node metastasis. Conclusion: It is necessary to have a comprehensive database of genomic alterations of colorectal carcinomas to interpret mutations more accurately clinically. There are no studies on the frequency of mutations in colorectal carcinomas in the Turkish population; thus, follow-up and treatment protocols are organized following the European and American databases and guidelines. A comprehensive study of the colorectal carcinoma patients’ mutation profile in the Turkish patient cohort by the next-generation sequencing method will help to provide significant therapeutic, prognostic, and predictive data and design more successful treatment and follow-up strategies.